FEEDING FREQUENCY ITS ACTION ON VIABILITY OF PRODUCTION AND PARASITE LOAD IN Pterophyllum scalare - Fujimoto, Rodrigo Yudi; Santos, Rudã Fernandes Brandão; Honorato, claucia Aparecida; Dias, Henrique Malta; Ramos, Fabrício Menezes; Silva, Derlan José Ferreira (Archives of Veterinary Science, 2015)
Angelfish (Pterophyllum scalare) is a very important species in Brazil’s domestic market, enjoying feeding managements that differ from fish breeders to aquarists, so the cost of feed and labor become relevant items when cultivating the species. Thus, the objective of this work was to assess feeding frequency and feed deprivation based on growth performance, parasite infestation and cost-benefit in farming the species. The experiment was conducted in a completely randomized design in a 3x2 factorial scheme with 3 daily feeding levels, 4 meals, 2 meals and 1 meal; with and without feed deprivation and two repetitions. Feed deprivation consisted of offering feed 5 days a week only. Considering the performance, we observed that feeding once a day is the management of choice when the objective is maintaining fish weight. Feeding twice a day without deprivation and four times a day with or without feed deprivation resulted in higher growth performance than feeding once a day. Monogenean and nematode loads were not influenced by feeding management. The cost-benefit analysis enabled us to observe that the treatment with the best benefit was the one involving two feedings a day with no deprivation. Thus, considering the parameters mentioned above, we concluded that the treatment consisting of two daily feedings with no feed deprivation is the most adequate for farming this specie.